2019
DOI: 10.1002/rse2.126
|View full text |Cite
|
Sign up to set email alerts
|

From ecology to remote sensing: using animals to map land cover

Abstract: Land cover is a key variable in monitoring applications and new processing technologies made deriving this information easier. Yet, classification algorithms remain dependent on samples collected on the field and field campaigns are limited by financial, infrastructural and political boundaries. Here, animal tracking data could be an asset. Looking at the land cover dependencies of animal behaviour, we can obtain land cover samples over places that are difficult to access. Following this premise, we evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Mapping of vegetation in built-up areas (i.e., forest, low vegetation) showed a better classification accuracy based on MT imagery (Table 3 and Figure 4). We used F1 and FoM accuracy metrics as macro-averaged measures that were suitable for evaluating the accuracy of various land-cover classes [69,75,94]. Table 3 shows an improvement in different classification scenarios for discriminating various land-cover classes, especially forest and low vegetation (i.e., grassland, shrubs).…”
Section: Discussionmentioning
confidence: 99%
“…Mapping of vegetation in built-up areas (i.e., forest, low vegetation) showed a better classification accuracy based on MT imagery (Table 3 and Figure 4). We used F1 and FoM accuracy metrics as macro-averaged measures that were suitable for evaluating the accuracy of various land-cover classes [69,75,94]. Table 3 shows an improvement in different classification scenarios for discriminating various land-cover classes, especially forest and low vegetation (i.e., grassland, shrubs).…”
Section: Discussionmentioning
confidence: 99%
“…For researchers who monitor ecological environment quality (EEQ), the information is a very useful data source. A previous study suggested that remote sensing technology plays an important role in monitoring atmospheric pollutants in natural or anthropogenic ecosystems [14]. In Sweden, remote sensing technology was also used to quantitatively evaluate urban growth impacts on the provisioning of urban ecosystem services [15].…”
Section: Introductionmentioning
confidence: 99%